RHYMES FOR ANNIE ROSE - Shirley Hughes (India Random House UK, 1995)
An illustrated collection of poetry, centring around the life of Annie Rose, Alfie's little sister. There are poems for quiet times, poems for busy times and poems about all aspects of a child's everyday life.
Keywords: Poetry -- Read Aloud